Intimate partner violence during pregnancy and postpartum depression among married women in Putalibazar municipality. - Sharma,Rakshya (2020)
ABSTRACT: Introduction: Intimate Partner Violence (IPV) is the most common form of Violence, faced by women. In recent years, violence during pregnancy is increasingly being recognized as a significant problem in the developing world due to its adverse health consequences on both pregnant women and child. The objective of the study is to measure the magnitude of intimate partner violence during pregnancy and postpartum depression, factors associated with IPV and the effect of IPV in developing PPD. Methodology: A community based cross-sectional study was conducted in between October 2019 to December 2020 among 263 married women of extended postpartum period in Putalibajar municipality, Syanjga District, Western Nepal. Face to face, interview was conducted to collect the information. IPVDP was assessed using a structured questionnaire of World Health Organization(WHO) and the Edinburgh Postnatal Depression Scale(EPDS) measured postpartum depression. Chi-square test was performed to assess the association between IPVDP and independent variables and regression was used to assess the strength of association. Results: Among 263 women interviewed, 30% experienced IPVDP, the most common type of violence was controlling behavior (20.2%) followed by emotional (18.6%), sexual (10.6%), economical (6.1%) and physical violence (5.3%). It was observed that IPVDP was more likely to occur among women who belonged to joint family(UOR= 2.36; CI 95%: 1.3 -4.184), Dalit ethnicity (UOR = 2.9;CI 95%: 1.451-5.796), women with less than 10 years of schooling (UOR = 1.943;CI 95%: 1.073-3.519), Women whose husband consumed alcohol (UOR + 3.526;CI 95%: 2.025-6.139), Women whose husband consumed tobacco (UOR = 3.959;CI 95% : 2.187-7.265), Women whose husband involved in gambling (UOR = 2.512;CI 95%:1.385-4.556), women who never received family support during pregnancy(UOR=5.962 ;CI 95%: 1.406-25.271) and women who did not decide upon their marriage timing (UOR =2.739; CI 95%: 1.587- 4.727). The prevalence of postpartum depression was 10.6% using EPDS score above 13. Women reporting and IPVDP had increased odds of PPD (UOR= 7.289;CI 95% 2.541-20.911). Conclusion: Three out of ten pregnant women experienced IPVDP and it was strongly associated with postpartum depression. To prevent violence, educating young people about respectful relationship, ensuring women's empowerment by focusing on higher educational opportunities as well as discouraging the element of violent milieu is important. Appropriate laws prohibiting violence to women and actions regarding screening of IPV during pregnancy at antenatal visits with proper management and referral to relevant care is needed. Keywords: Intimate partner violence, partner abuse, partner violence, postpartum depression, pregnancy spousal violence.